Predictors of place of death in South West Scotland 2000–2010: Retrospective cohort study. (September 2016) - Black, Heather; Waugh, Craig; Munoz-Arroyo, Rosalia; Carnon, Andrew; Allan, Ananda; Clark, David; Graham, Fiona; Isles, Christopher
Background: Surveys suggest most people would prefer to die in their own home. Aim: To examine predictors of place of death over an 11-year period between 2000 and 2010 in Dumfries and Galloway, south west Scotland. Design: Retrospective cohort study. Setting/Participants: 19, 697 Dumfries and Galloway residents who died in the region or elsewhere in Scotland. We explored the relation between age, gender, cause of death (cancer, respiratory, ischaemic heart disease, stroke and dementia) and place of death (acute hospital, cottage hospital, residential care and home) using regression models to show differences and trends. The main acute hospital in the region had a specialist palliative care unit. Results: Fewer people died in their own homes (23.2% vs 29.6%) in 2010 than in 2000. Between 2007 and 2010, men were more likely to die at home than women ( p  < 0.001), while both sexes were less likely to die at home as they became older ( p  < 0.001) and in successive calendar years ( p  < 0.003). Older people with dementia as the cause of death were particularly unlikely to die in an acute hospital and very likely to die in a residential home ( p  < 0.001). Between 2007 and 2010, an increasing proportion of acute hospital deaths occurred in the specialist palliative care unit (6% vs 11% of all deaths in the study). Conclusion: The proportion of people dying at home fell during our survey. Place of death was strongly associated with age, calendar year and cause of death. A mismatch remains between stated preference for place of death and where death occurs.